2016
DOI: 10.1080/01694243.2016.1184411
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of structural, morphological alterations, wettability characteristics and adhesion to enamel after various surface conditioning methods

Abstract: Minimal invasive dental reconstructions and orthodontic appliances are bonded to enamel without removing the enamel with rotating instruments but the top layer of enamel may be partially aprismatic and impair adhesion. The objectives of this study were to investigate the effect of mechanical surface conditioning methods for removing enamel on its structural, morphological alterations, wettability characteristics and adhesion of resin based cement to the conditioned surfaces. Maxillary human incisors (N=40, n q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…The inferior etch quality in the cervical region can be explained by aprismatic enamel, which is orientated parallel rather than perpendicular to the enamel surface. 2,4,5 If the etchant cannot penetrate the full thickness of prismless enamel, a poor etch quality should be expected. This is why pretreatment mechanical abrasion of the tooth enamel, which removes the aprismatic enamel and exposes the underlying prismatic enamel, improves etch quality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferior etch quality in the cervical region can be explained by aprismatic enamel, which is orientated parallel rather than perpendicular to the enamel surface. 2,4,5 If the etchant cannot penetrate the full thickness of prismless enamel, a poor etch quality should be expected. This is why pretreatment mechanical abrasion of the tooth enamel, which removes the aprismatic enamel and exposes the underlying prismatic enamel, improves etch quality.…”
Section: Discussionmentioning
confidence: 99%
“…2 The prismless layer has an optic axis nearly parallel to the enamel's surface. [2][3][4][5] In contrast, prismatic enamel has distinct rod boundaries oriented perpendicular to the surface. The aprismatic enamel is believed to be due to decreased ameloblast activity during tooth development and the disappearance of Tomes' processes during the end of amelogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning debonding, it was shown that the use of rubbers for the removal of residual composites in orthodontic appliances was more effective compared to the use of discs. In summary, composite resins improve the bonding strength of orthodontic brackets, but conservative removal methods would be needed to reduce damage to tooth enamel 17,18,20,23,24,28,33,38,41 . Other studies analyzed other materials than those mentioned, including the adhesive residue remover and the tungsten carbide bur, which is the most aggressive for enamel.…”
Section: Studies That Include Adhesive Adaptation Techniquesmentioning
confidence: 99%